CORRELATION BETWEEN ETHAMBUTOL THERAPY DURATION AND ZINC SERUM LEVEL WITH COLOUR VISION DEFICIENCY IN TUBERCULOSIS PATIENTS - Devi Azri Wahyuni; Mira Retna Tetiana; Mgs Irsan Saleh; Ahmad Rasyid (Majalah Kedokteran Sriwijaya, 2020)
Tuberculosis is one of the most common disease in Indonesia. Ethambutol is one of the main regiment therapy for patient with tuberculosis. Duration of ethambutol therapy depends on what category of tuberculosis patient. Ethambutol intake can cause optic neuropathy with colour vision deficiency as an early symptom. Ethambutol therapy can also cause decrease of zinc serum level and it is cause by zinc chelate that can be found in ethambutol. The purpose of this study was to determine the correlation between duration of ethambutol therapy and zinc serum level with colour vision deficiency which examined with Farnsworth Munsell 100 Hue in tuberculosis patients. This is an observational explorative study. Colour vision is xamined with Farnsworth Munsell 100 Hue and zin serum level is detected by blood sample. Data was analyzed by correlation study. Correlation statistic between ethambutol therapy duration with colur vision using Spearman coreelation study found that r = 0,5 and p = 0,00, whereas in correlation between zinc serum level with colour vision found that r = 1,68 and p = 0,32. There is significant correlation and positive direction between ethambutol therapy duration with colour vision deficiency. Even though there is no significant correlation between zinc serum level with colour vision deficiency, there is a strong correlation.